Fashioning Jews : Clothing, Culture and Commerce (SJC #24) - Greenspoon, Leonard J. (Leonard Jay); Project Muse. (West Lafayette, Ind. : Purdue University Press, 2013)
This volume presents papers delivered at the 24th Annual Klutznick-Harris Symposium, held at Creighton University in October 2011. The contributors look at all aspects of the intimate relationship between Jews and clothing, through case studies from ancient, medieval, recent, and contemporary history. Papers explore topics ranging from Jewish leadership in the textile industry, through the art of fashion in nineteenth century Vienna, to the use of clothing as a badge of ethnic identity, in both secular and religious contexts.
Ella Zirner-Zwieback, Madame d'Ora, and Vienna's New WomanPhotographers, Jews, and the Fashioning of Women in the Weimar Republic; Weimar Jewish Chic: Jewish Women and Fashion in 1920s Germany; Unbuttoned: Clothing as a Theme in American Jewish Comedy; "What a Strange Power There Is in Clothing": Women's Tallitot; Aboriginal Yarmulkes, Ambivalent Attire, and Ironies of Contemporary Jewish Identity.
Description based on print version record.
Keywords: Bekleidungsindustrie; Juden; Kleidung; Jews -- Civilization; Jewish clothing and dress; DESIGN -- Textile & Costume; SOCIAL SCIENCE -- Jewish Studies; Juifs -- Civilisation; Costume juif -- Histoire; Costume juif; Jews -- Civilization; Jewish clothing and dress -- History; Jewish clothing and dress; History; Electronic books